Treatment of Distal Ureteric Stones- Comparative Efficacy of Transurethral Pneumatic Lithotripsy and Extracorporeal Shock Wave Lithotripsy - Khan, Jamil Ahmed (Biological and Clinical Sciences Research Journal, 2025)
Ureteric stones are treated with two minimally invasive procedures: transurethral pneumatic lithotripsy and extracorporeal shock wave lithotripsy. Objective: This study aimed to find out the comparative efficacy of transurethral pneumatic lithotripsy and extracorporeal shock wave lithotripsy in the treatment of distal ureteric stones. Method: The present randomized controlled study was conducted at the Department of Urology, Postgraduate Medical Institute (PGMI), Quetta, from January 2025 to June 2025, after obtaining approval from the institute’s ethical board. A total of 232 individuals presented to OPD, following a thorough clinical assessment (history, examination, pertinent tests such as urine culture, X-ray KUB, ultrasound KUB, and excretory urography) of different age groups and both genders who had distal ureteric stones ranging in size from 6 to 12 mm, were included in this study. The study participants were equally divided into two groups: Group A received TPL (transurethral pneumatic lithotripsy), and Group B received ESWL (extracorporeal shock wave lithotripsy) treatment. Two weeks following the procedure, each patient underwent monitoring with an ultrasound and a KUB X-ray. The procedure was considered effective if the X-ray KUB revealed no stones or fragments less than four millimeters in diameter, as these are meant to pass through the urine, or if the ultrasound revealed no stones. All of the data was entered into a pre-made pro forma. SPSS 10.0 was used to analyze the data. For quantitative characteristics, such as stone size and age, the mean ± SD was computed. For categorical factors, such as efficacy and gender, percentages and frequencies were calculated. The effectiveness of the treatment methods was compared using Fisher’s exact test. A p-value of less than 0.05 was considered significant. Results: A total of 232 individuals were enrolled in this study. The overall male-to-female ratio was 2.2:1. The mean age in Group A was 46.74±16.24 years, and in Group B, it was 44±13.57 years. The study found that the majority of our ureteric stone participants (30.6%) were between the ages of 31 and 45. Groups A and B each had 38 (32.7%) and 35 (30.1%) stones that were 6–8 mm in size. Extracorporeal Shock Wave Lithotripsy was successful in 80 (69%) of the individuals at the 2-week follow-up, whereas transurethral pneumatic lithotripsy was effective in 111 (95%) of the participants. P-value was statistically significant (p < 0.0001). Conclusion: The present study concluded that TPL was effective in 95% of participants, indicating it is superior to ESWL in treating distal ureteric stones.